DEVELOPING THE SKILLS OF WRITING GERMAN PARAGRAPH THROUGH THE MODEL OF COOPERATIVE LEARNING WITH JIGSAW TEHNIQUE (Action Research in MAN 2 Kota Serang ) - Mahfuroh Mahfuroh; Emzir Emzir; Fahrurrozi Fahrurrozi (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
AbstractThe objective of this research is developing the skills of writing paragraph through the model of cooperative learning with jigsaw technique. The objects of this study were the students of Islamic state high school 2 Kota Serang on the XI grade of language program in the second semester academic year 2015/2016 amounting to 32 students.The instrument of data collection was early test, questioner, observation, collaborator arguments and final test and the technique of data analysis were descriptive quantitative and descriptive qualitative techniques. This research was an action research with 3 cycles and each cycle consist of threemeetings. At the end of each learning cycle each student was given an individual writing test and the results of this test become the basis of the success of a research action. The results of activities in this study stated that there is an increase both in process and improvement of student learning outcome.This is evidenced by the student’s writing results from average increase obtained from the first cycle to the third cycle.Teaching using cooperative learning model with jigsaw technique is an effective and appropriate learning model and it can maximize the learning outcome, one of them is improving the skill of writing German paragraph.Key words : skills of writing paragraph, cooperative learning model, jigsaw